Limited Proteolysis, Evaluating the Degree of Hydrolysis and Molecular Weight Profile of Protein Hydrolysates from Vigna subterranea and Cajanus cajan - Amponsah, Afia Sakyiwaa (2015)
A Thesis Submitted To the Department Of Food Science and Technology in Partial Fulfilment of the Requirements for the Award of the Degree Of Master of Science in Food Science and Technology, 2014